Mental Disorder and Criminal Law Responsibility, Punishment and Competence - Schopp, Robert; Wiener, Richard L.; Bornstein, Brian H.; Willborn, Steven L. (Springer New York : Imprint: Springer, 2009)
The death penalty has long played a central role in jurisprudence, in terms of identifying the most serious offenses and the most culpable offenders, as well as understanding the mental conditions that may exclude an offender from such a sentence. More recently, the debate has intensified on competency to face [execution], the effects of psychological impairment on that competency, and the role of expert witnesses in establishing criminal culpability. The edited volume, Mental Disorder and Criminal Law authoritatively blends empirical findings and legal expertise with sophisticated reasoning and ethical analysis to promote a deeper understanding of these complex issues at the interface of legal and psychological domains. In short, it explores the concept of (as termed by one chapter author) "protecting well-being while pursuing justice." Contributors to this important volume: Examine the effects of depression at different stages of legal procedure. Offer proposed criteria for [prohibiting] capital punishment [of] the severely mentally ill Identify moral and procedural concerns in the use of child victims as witnesses. Analyze the balance between present responsibility and future risk. Untangle clinical and ethical issues for clinicians involved in capital sentencing. Clarify the process of psychological evaluation of competence to be executed. Review degrees of psychopathy in the context of criminal culpability. A practice-enhancing reference for forensic psychiatrists and psychologists, and legal professionals, Mental Disorder and Criminal Law challenges readers to reexamine the life-and-death questions at the core of their work.